Deep Trade Policy Options for Armenia : The Importance of Services, Trade Facilitation and Standards Liberalization - Jensen, Jesper; Tarr, David G. (2012)
This paper develops an innovative 21 sector computable general equilibrium model of Armenia to assess the impact on Armenia of a Deep and Comprehensive Free Trade Agreement with the European Union, as well as further regional or multilateral trade policy commitments. The analysis finds that such an agreement with the European Union will likely result in substantial gains to Armenia, but shows that the gains derive from the deep aspects of the agreement. In order of importance, the sources of the gains are: (i) trade facilitation and reduction in border costs; (ii) services liberalization; and (iii) standards harmonization. A shallow agreement with the European Union that focuses only on preferential tariff liberalization in goods will likely lead to small losses to Armenia primarily due to a loss of productivity from lost varieties of technologies from the rest of the world region in manufactured products. Additional gains can be expected in the long run from an improvement in the investment climate. The authors estimate only small gains from a services agreement with countries of the Commonwealth of Independent States, but significant gains from expanding services liberalization multilaterally.